PENGARUH PENGETAHUAN PAJAK DAN PERSEPSI WAJIB PAJAK TERHADAP KEPATUHAN WAJIB PAJAK - Supriyati Supriyati (Universitas Hayam Wuruk Perbanas, 2011)
The Directorate General of Taxation has done a strategic role. One of the activities is to increase the tax payer's compliance. This research attempts to see the influence of tax knowledge, tax payer perception of 'fiscus